INTEGRASI REGULASI, TATA KELOLA, DAN DIGITALISASI DALAM PERBANKAN SYARIAH: ANALISIS IMPLEMENTASI HUKUM EKONOMI SYARIAH DI INDONESIA - Zikri Mahyar (LEMBAGA PENELITIAN DAN PENGABDIAN PADA MASYARAKAT, 2025)
The Islamic banking industry in Indonesia has experienced rapid growth, with total assets reaching IDR 980.30 trillion by the end of 2024. However, its market share remains only around 7–8% of total national banking assets, indicating a gap between potential and actual realization. This study aims to analyze the implementation of Islamic economic law in Islamic banking transactions, focusing on regulations, governance, and practical challenges in the field. The legal framework is based on Law No. 21 of 2008 on Islamic Banking, Supreme Court Regulation No. 2 of 2008 on the Compilation of Islamic Economic Law (KHES), and the DSN-MUI fatwas governing Islamic contracts. The role of the Sharia Supervisory Board (DPS) is crucial in ensuring internal compliance, while BASYARNAS-MUI serves as an arbitration institution for dispute resolution. Although regulations are comprehensive, challenges persist in implementation, including limited product innovation, relatively high funding costs, human resource quality, and digital integration complexity. This research applies a qualitative juridical-normative approach, analyzing primary data such as regulations and fatwas, and secondary data from official reports and academic literature. The findings highlight the importance of Islamic Corporate Governance, process-based compliance, and strengthened digital regulations to ensure innovations remain aligned with sharia principles. This study contributes academically through an integrative analysis between sharia law and digitalization, while also providing practical recommendations for regulators, industry, and judiciary institutions.